(untitled) (Cybersecurity and Network Defense Research, 2022)
Integration of Sign-On (SSO) in cloud based DevOps environment is marked as a crucial development in enhancing security for Continuous Integration and Continuous Deployment (CI/CD) pipeline. As DevOps speedup software delivery through automation the expansion of access point and user credentials introduces various security vulnerabilities such as credential sprawl, unauthorized access, and compliance risks. Through the implementation of SSO organisations can centralize authentication, enforce stringent access controls, and reduces identity-based threats mean while improving developer productivity. This research paper aims to provide a technical analysis of SSO integration in CI/CD workflow and the impact on authentication mechanisms, role-based access control (RBAC), and secure secrets management.